Impact of heat source/sink on radiative heat transfer to Maxwell nanofluid subject to revised mass flux condition - Khan, M.; Irfan, M.; Khan, W.A. (Results in physics, 2018)
•Maxwell fluid over a stretched cylinder is established.•Impact of thermal radiation and heat source/sink are considered.•Brownian and thermophoresis nanoparticles.•Nanoparticles mass flux condition.•Analytical (HAM) technique. Nanofluids retain noteworthy structure that have absorbed attentions of numerous investigators because of their exploration in nanotechnology and nanoscience. In this scrutiny a mathematical computation of 2D flows of Maxwell nanoliquid influenced by a stretched cylinder has been established. The heat transfer structure is conceded out in the manifestation of thermal radiation and heat source/sink. Moreover, the nanoparticles mass flux condition is engaged in this exploration. This newly endorsed tactic is more realistic where the conjecture is made that the nanoparticle flux is zero and nanoparticle fraction regulates itself on the restrictions consequently. By utilizing apposite conversion the governing PDEs are transformed into ODEs and then tackled analytically via HAM. The attained outcomes are plotted and deliberated in aspect for somatic parameters. It is remarked that with an intensification in the Deborah number β diminish the liquid temperature while it boosts for radiation parameter Rd. Furthermore, the concentration of Maxwell liquid has conflicting impact for Brownian motion Nb and thermophoresis parameters Nt.